The Influence of Price Perception and Customer Experience on Purchase Intention Mediated by Customer Satisfaction (Empirical Study: Haidilao Restaurant Consumers in Jakarta) - Chelsea, Chelsea; Bambang Sugiyanto, Liem (Pelopor Publikasi Akademika, 2024)
The purpose of this research is to analyze further the relationship and influence of price, customer experience on purchase intentions which is mediated by customer satisfaction on purchase intentions at the HaiDiLao restaurant. The method used in this research is a quantitative method and was processed using AMOS. The survey was conducted on 155 respondents who met the respondent criteria using non-probability sampling. The research found that price perception, customer experience, and customer satisfaction did not significantly influence the purchase intention. Meanwhile, price perception and customer experience had a significant influence on customer satisfaction. On the other hand, price perception and customer experience also did not significantly influence purchase intention. The limitation of the research was the limited respondents, with 155 respondents domiciled in Jakarta who have visited HaiDiLao restaurant in Jakarta. This research could be generalized more widely if the samples were taken not only from Jakarta City. The implications of this research provided managerial contributions to the food and beverages industry, especially an overview of customer experience and an understanding of the factors influencing increased purchase intentions, such as price perception, customer experience, customer satisfaction, and purchase intention. So, managers can develop a business strategic plan that aligns with internal and external company conditions.